2017
DOI: 10.3390/catal7120387
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Addition of Me2Zn to Isatins

Abstract: Chiral α-hydroxyamide L5 derived from (S)-(+)-mandelic acid catalyzes the enantioselective addition of dimethylzinc to isatins affording the corresponding chiral 3-hydroxy-3-methyl-2-oxindoles with good yields and er up to 90:10. Furthermore, several chemical transformations were performed with the 3-hydroxy-2-oxindoles obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…On the other hand, when 1-(4-methoxyphenyl)-2-(4-(trifluoromethyl)phenyl)ethane-1,2-dione 5b acted as the electrophile, the product 6b was obtained as a single regioisomer, as a result of the alkynylation of the carbonyl attached to the electronically deficient aromatic ring (Table 5, entry 3). The alkynylation also proceeds with total regioselectivity if there are two electron-withdrawing chlorine substituent group (Table 5, entries [8][9][10] or two electrondonating methoxy groups in one of the aromatic rings (Table 5, entries 4-7). In all cases the enantioselectivity was good.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when 1-(4-methoxyphenyl)-2-(4-(trifluoromethyl)phenyl)ethane-1,2-dione 5b acted as the electrophile, the product 6b was obtained as a single regioisomer, as a result of the alkynylation of the carbonyl attached to the electronically deficient aromatic ring (Table 5, entry 3). The alkynylation also proceeds with total regioselectivity if there are two electron-withdrawing chlorine substituent group (Table 5, entries [8][9][10] or two electrondonating methoxy groups in one of the aromatic rings (Table 5, entries 4-7). In all cases the enantioselectivity was good.…”
Section: Resultsmentioning
confidence: 99%
“…3 The utilization of activated ketones bearing an electronwithdrawing-group in alpha position to the carbonyl group overcome these problems of lack of reactivity, as shown in the enantioselective alkylation and alkynylation to α-ketoesters 4,5 fluorinated ketones, 6,7 and isatines. 8,9 However, this excess of reactivity along with the fact that, many times, this particular kind of electrophile may act as a chelating ligand and enhance the reactivity of the nucleophilic species, might be a problem due to the competing non-catalyzed reaction pathway, which would have a detrimental effect on the enantioselectivity. Recently, we have shown that chiral conformationally restricted perhydro-1,3-benzoxazines derived from (-)-8-aminomenthol behave as excellent ligands for the enantioselective addition of organozinc reagents to carbonyl compounds, 10 including αketoesters.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, there are few methods for the catalytic asymmetric synthesis of chiral 3‐hydroxy‐3‐methyl‐2‐oxindoles in previous report [16] . Shibashaki [16d] and Pedro's group [16e] reported the enantioselective addition of Me 2 Zn to isatins catalyzed by proline‐derived aminodiol and α‐hydroxyamides ligand, respectively, and only moderate ee values were obtained. We performed the reaction between N ‐substituted isatins 4 and Me 2 Zn in the presence of DCM at −40 °C.…”
Section: Methodsmentioning
confidence: 99%
“…However, when the protecting group was electron‐withdrawing group such as acetyl, the product 5 m was obtained in moderate yield, albeit with high ee . The absolute configuration of 5 was determined by comparison to reported literature [16e] …”
Section: Methodsmentioning
confidence: 99%